CHANGE MANAGEMENT IN EDUCATION: ADAPTATION AND VALIDATION OF THE ORGANISATIONAL CHANGE CAPACITY SCALE (Third Sector Social Economic Review, 2025)
This study aims to measure perceptions of change capacity in educational organizations reliably and validly. To achieve this objective, Organizational Change Capacity Scale (OCCS) was adapted from a foreign language into mother tongue, following the necessary steps for scale adaptation/development. These steps were completed alongside validity and reliability tests. During this process, statistical methods such as Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were utilized. The data were collected from 167 provincial branch managers and 310 high school administrators working in the Ministry of National Education (MoNE). The steps involved in the scale development process were assessed in conjunction with the research findings. Participants’ perceptions of change capacity were analyzed based on demographic variables such as gender, age, title, marital status, geographical region. Statistical techniques such as t-tests and ANOVA were employed in these analyses. The research findings indicate that OCCS is not only a valid measurement tool for educational organizations but also applicable to other sectors. Additionally, the scale was found to be a valid instrument for assessing change capacity. This study is considered to provide a scientific foundation for evaluating the change capacity of institutions and organizations. It is also believed that the research findings contribute significantly to the academic literature and provides valuable insights for decision-makers.
Keywords: Change Capacity; Educational Organisations; 10-Point Likert Scale; Statistical Analysis